Fatty Acid and Cholesterol Concentrations in Usually Consumed Fish in Brazil - Scherr,Carlos (2015)
Background: Several studies have demonstrated clinical benefits of fish consumption for the cardiovascular system. These effects are attributed to the increased amounts of polyunsaturated fatty acids in these foods. However, the concentrations of fatty acids may vary according to region. Objective: The goal of this study was to determine the amount of,cholesterol and fatty acids in 10 Brazilian fishes and in a non-native farmed salmon usually consumed in Brazil. Methods: The concentrations of cholesterol and fatty acids, especially omega-3, were determined in grilled fishes. Each fish sample was divided in 3 sub-samples (chops) and each one was extracted from the fish to minimize possible differences in muscle and fat contents. Results: The largest cholesterol amount was found in white grouper (107.6 mg/100 g of fish) and the smallest in badejo (70 mg/100 g). Omega-3 amount varied from 0.01 g/100 g in badejo to 0.900 g/100 g in weakfish. Saturated fat varied from 0.687 g/100 g in seabass to 4.530 g/100 g in filhote. The salmon had the greatest concentration of polyunsaturated fats (3.29 g/100 g) and the highest content of monounsaturated was found in pescadinha (5.98 g/100 g). Whiting and boyfriend had the best omega-6/omega 3 ratios respectively 2.22 and 1.19, however these species showed very little amounts of omega-3. Conclusion: All studied Brazilian fishes and imported salmon have low amounts of saturated fat and most of them also have low amounts of omega-3.